Wykorzystanie controllingu w kreowaniu wartości banku - Korzeb, Zbigniew (The usage of controllership in a bank value creation, 2006)
The usage of modem controllership methods is the fundamental support for strategic management in a commercial bank. Effective management calls for management accounting techniques. They help to achieve the ultimate goal of a bank’s activity - the maximizing of the bank’s value. Value driver analysis gives support for decision making, planning, performance evaluation, incentive compensation, resource utilization and indicate the most profitable customers, products and services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 196-202